15.09 Examining the neurological consequences of new psychoactive substances -'legal highs'. Issue 12 (14th November 2019) - Jones, Rebekah; Kelleher, Charles; Tanti, Matthew; Cosgrove, Jeremy; Maguire, Melissa
Abstract : Background: New psychoactive substances (NPS) are of global concern accounting for increasing deaths in the UK. We conducted a retrospective analysis of patients attending Leeds Teaching Hospitals NHS Trust with NPS abuse during 2016–2017 and report neurological presentations and outcomes. Methods: We identified 227 records of NPS attendances through electronic searches using Symphony electronic software. Demographic and clinical data were obtained from case-note review. Results: Average age was 34, 82% were male. Two thirds were unemployed, 17% prisoners, 9% students and 4% prison workers. 'Spice' accounted for the majority of presentations (90%). 4-methyl methcathinone ('MCAT') accounted for 8% of presentations. The remainder reported nitrous oxide (NOS) use. In the spice subgroup, 52% had low GCS, 20% had seizures. Ventilatory support was required in two cases (1%). In the MCAT subgroup, average GCS was 14 and 20% of patients presented with seizure. Psychiatric disturbance was higher in MCAT group (30%). Most patients (62%) were observed in the emergency department and then discharged. Only 3% were referred to the drug and alcohol team. Conclusions: Spice accounted for the majority of NPS presentations. Unemployed single men were particularly at risk. Low GCS and seizures were the commonest presentations, with most requiring observation only.